Reactions of cowpea to infection by Macrophomina phaseolina isolates from leguminous plants in Nigeria - Amusa, N.A.; Okechukwu, R.; Akinfenwa, B. (2007)
The reaction of cowpea to infection by Macrophomina phaseolina isolates, from leguminous plants in Nigeria, was investigated at Ibadan, southwestern Nigeria. M. phaseolina isolates obtained from six different leguminous species induced necrotic lesions of varying sizes on two cowpea varieties, IT83D-340 and IT84D-488. Isolate 93-295 from winged bean (Psophocarpus tetragonoloteus) leaf tissues was the most virulent, inducing necrotic lesions of 4.8 mm in diameter on cowpea stem tissues while the smallest necrotic lesion size of 3.2 mm was induced on the same cowpea by isolate 93-52-1. This suggests that cowpea varieties are highly susceptible to M. phaseolina isolates from six different legumes. Moreover, the reactions of the two-cowpea varieties to M. phaseolina isolates from the six legumes differ significantly. This suggests that differences exist in the susceptibility of cowpea varieties to the pathogen.